Sergiy Petrovych Osinsky (1945–2015) (Experimental Oncology, 2015)
Professor Sergiy Petrovych Osinsky, an outstanding
scientist, oncologist and pathophysiologist, Head
of Department of the Microenvironment of Tumor Cells
of the R.E. Kavetsky Institute of Experimental Pathology,
Oncology and Radiobiology (IEPOR) of the NAS
of Ukraine, died on May 21, 2015, at the age of 69.